Characterization of 15 polymorphic microsatellite loci in Rimicaris exoculata, and cross-amplification in other hydrothermal-vent shrimp - Teixeira, Sara (2014)
Abstract Rimicaris exoculata is an alvinocarid shrimp endemic to the hydrothermal vents of the Mid-Atlantic Ridge. In order to study genetic variability and connectivity in this species, we developed fifteen polymorphic microsatellite markers. The markers were tested on one population and, except for one, all showed no departure from Hardy–Weinberg equilibrium, with an average overall observed heterozygosity of 0.63. Two primer pairs revealed possible linkage disequilibrium, and 14 crossamplified at least one of the three co-occurring shrimp species tested (Alvinocaris muricola, Alvinocaris markensis and Mirocaris fortunata). These markers therefore open perspectives for population genetic studies of hydrothermal vent shrimp species in order to unravel connectivity and evolution of populations, and to add information on possible future impact studies.